2021
DOI: 10.1111/jocd.13943
|View full text |Cite
|
Sign up to set email alerts
|

Development of the facial glycation imaging system for in situ human face skin glycation index measurement

Abstract: Background The accumulation of advanced glycation end products has been proposed as a causative agent of skin aging, but there are no conventional devices for quantifying advanced glycation end‐product accumulation in facial skin. Aims This study aimed to develop a convenient and accurate in situ advanced glycation end‐product measurement system for the human face. Methods We developed a facial glycation imaging system, which consisted of illumination (white light‐emitting diode, ultraviolet light‐emitting dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…The facial glycation imaging system (FGIS) was developed by Lee et al ( 88 ) for the determination of the human facial skin glycation index. After the system collects facial images, it uses image analysis algorithms to calculate the autofluorescence of AGEs and the total skin reflectance to give the skin glycation index.…”
Section: Skin Advanced Glycation End Products Measurement Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The facial glycation imaging system (FGIS) was developed by Lee et al ( 88 ) for the determination of the human facial skin glycation index. After the system collects facial images, it uses image analysis algorithms to calculate the autofluorescence of AGEs and the total skin reflectance to give the skin glycation index.…”
Section: Skin Advanced Glycation End Products Measurement Methodsmentioning
confidence: 99%
“…After collagen and AGEs are cross-linked, the fibre deformation reaches more than 80% of all tissue deformation, resulting in a loss of obvious stress relaxation behaviour ( 86 ). The full-thickness restructuring skin model of Lee et al ( 88 ) showed that the yellowness of the skin increases with increasing AGEs (CML). Laughlin et al ( 87 ) collected female skin samples to determine the content of AGEs, and the number of AGEs was significantly higher in people with dull and yellow skin.…”
Section: Various Advanced Glycation End Products Damage Different Lev...mentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, glycation in vivo causes skin AGEs to accumulate, resulting in wrinkles, loss of elasticity, dullness, and decreased function of skin, which is one of the main mechanisms of skin aging [ 67 ]. AGEs cause pathological changes in the skin through three processes.…”
Section: The Hazards Of Skin Glycationmentioning
confidence: 99%
“…The most important concentrations of AGEs in the skin are (from the highest to the lowest concentrations) glucosepane, CML, pentosidine, and CEL [ 68 ]. Skin autofluorescence (SAF) has been shown to be a biomarker of cumulative skin AGEs [ 69 ], and measuring facial fluorescence intensity allows for an assessment of the skin glycation index [ 67 ]. SAF is also a powerful and independent predictor for cardiovascular disease and type 2 diabetes (T2D) [ 70 ].…”
Section: The Hazards Of Skin Glycationmentioning
confidence: 99%